1995
DOI: 10.1063/1.114543
|View full text |Cite
|
Sign up to set email alerts
|

Dose loss in phosphorus implants due to transient diffusion and interface segregation

Abstract: For implanted phosphorus in the dose range of 5×1013/cm2–4×1014/cm2, up to half the implanted dose may be lost during low thermal budget anneals due to transient diffusion and anomalous segregation at the Si–SiO2 interface. The phosphorus atoms, rendered mobile by the implant damage, stick in the oxide near the interface where they are electrically inactive and can be removed by stripping the surface oxide. Such a dose loss needs to be accounted for in a typical device fabrication process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Loss of dopant dose from bulk Si to the Si/SiO interface has been reported in [10]- [12] with boron from BF implants being shown to be particularly susceptible to interface dose loss in [12]. The source-drain extension for the PFET's being studied here was indeed created by implantation of BF .…”
Section: Proposed Mechanismmentioning
confidence: 93%
“…Loss of dopant dose from bulk Si to the Si/SiO interface has been reported in [10]- [12] with boron from BF implants being shown to be particularly susceptible to interface dose loss in [12]. The source-drain extension for the PFET's being studied here was indeed created by implantation of BF .…”
Section: Proposed Mechanismmentioning
confidence: 93%
“…In fact, it was shown experimentally that the concentration of segregated dopants reaches a half Si monolayer at the interface. 15 The situation of dopant segregation to the Si/ SiO 2 interface is very similar to that of heavily doped Si; dopant atoms in both the cases are electrically deactivated. In bulk Si, it was reported that the maximum concentration of active dopants is no higher than 5 ϫ 10 20 cm −3 , 16-18 which gives the average dopant-to-dopant distance of about 12.6 Å.…”
mentioning
confidence: 92%
“…For example, it has long been known that dopant impurities such as As, P, and B segregate at the Si-SiO 2 interface. [2][3][4] Recently, however, atomically resolved Z-contrast imaging of stray Hf atoms inside the SiO 2 interlayer of Si/ SiO 2 / HfO 2 structures found that the Hf atoms avoid the Si-SiO 2 interface. [5][6][7] Such multilayer structures are widely studied as a possible replacement of pure SiO 2 as the gate dielectric in advanced microelectronics, whereby a fundamental understanding of the behavior of stray impurities and other defects has become important.…”
Section: Introductionmentioning
confidence: 98%